Evaluation of Bogie Bolster Centre Plate and Side Bearing under Vertical Static Loads through Finite Element (FEA) Modelling - I.P. Artha Wirawan; I.D.G Ary Subagia; I.K Adiatmika; A.R Farid (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
The bolster is one of the main structural elements in railway bogies, playing the central role of transmitting vertical and dynamic loads from the train body to the wheel-sets. The mechanical behavior of an ASTM A148 Grade 80-50 material bolster under vertical static loading is examined in this work. This simulation is analyzed by applying the Finite Element Analysis (FEA) using student version software with nonlinear static analysis, which was run with a tetrahedral mesh and Newton-Raphson iteration. There are three variables, respectively, two variables as dependent, such as Von Misses Stress (VMS) and total deformation resulting from the loading condition. Then, the independent variable is a loading value based on the AAR M-202 standard. In this work, three values of loading condition were carried out, such as P1 = 536010.7 N, P2 = 854058.8 N, P3 = 1027500 N respectively. The result of the simulation shows that the maximum average stress in the critical area is 305.58 MPa, which is still less than the yield strength of the material at 390 MPa. The maximum elastic deflection of 0.102 mm is well within the AAR M-202 standard allowable values. In conclusion, bolster bogie based on ASTM A148 Grade 80-50 has reliability for static loading and is available with a safety factor according to the AAR M-202 standard.